Patriarch Tarasios: An exponent of Byzantine church diplomacy in relation to Rome and the bishop of Constantinople - Nicolae, Chifar (HTS teologiese studies, 2021)
On September 24, 787, the works of the VII Ecumenical Synod were opened in the ‘Saint Sophia’ Church in Nicaea, after the first attempt, on August 7, 786, had failed. Although the nominal presidency was held by the legates of Pope Adrian I, the effective presidency was exercised by Patriarch Tarasios of Constantinople. A skilful church diplomat, with experience, gained as an imperial secretary and a remarkable theologian whose authority was imposed even during his election as a patriarch amongst the laity, Tarasios meticulously and clairvoyantly prepared for the deployment of the Nicene synod. This is noticeable from the agreement made with the papal legates regarding the reading of the letters of Pope Adrian I whose content directly concerned the persona of the patriarch, agreeing to omit those compromising paragraphs, from the procedure of re-welcoming in the communion of the church of some former iconoclastic bishops, by correctly managing the resistance of the monks to whom he gave satisfaction regarding the patristic and traditional argumentation of the cult of the holy icons and by rejecting point-by-point the dogmatic decision of the iconoclastic synod of Hieria (754), a rejection of which the patriarch Tarasie is in all probability the author. Satisfied with the success of the synod, whose craftsman he indeed was, Patriarch Tarasios was able to communicate to both Pope Adrian I and the emperors and clergy of Constantinople that the unity of the Church residing in Christ had been restored and that the place in the church and due honour of the holy icons had been restored through the synodal decision of 302 participants. The success of the Seventh Ecumenical Council is unequivocally because of the tactful and competent preparation and management of Patriarch Tarasios.Contribution: The perspective we promote on the events highlighted in the study, could contribute to unblocking the theological dialogue between Orthodox and Catholics on the issue of papal primacy, the study thus promotes HTS as an important forum for mediating interfaith dialogue.